An analysis of dimensional accuracy of clinical CT systems - Zippert, Patrick; Borges de Oliveira, Fabricio; Pirl, Lukas; Borowski, Markus; Binder, Felix; Hausotte, Tino (4th Dimensional X-ray Computed Tomography Conference, 2019)
Due to the steady improvement of computed tomography (CT), radiological diagnostics has become more and more effective. Among the various fields of application, precise dimensional measurements of anatomical parameters are clinically relevant e.g. to plan patient-individual implants or within radiotherapy. Despite the high potential of clinical CT systems for dimensional metrology, the accuracy of the measurements and the influence of the various acquisition and reconstruction parameters on the measurement error is mostly unconsidered in clinical practice. The constancy tests of clinical CT systems generally do not aim to check the dimensional accuracy of the systems. The dimensional verification of established measurement technologies such as coordinate measurement machines (CMMs) is usually performed by measurements on calibrated (i.e. traceable to the SI unit metre) reference standards. The aim of this investigation was to provide first results on the performance of different clinical CT and DVT systems in terms of dimensional accuracy by imaging a multi-sphere standard. This calibrated length standard is also used for a traceable length measurement error determination of industrial CT systems. The results indicate that different clinical CT protocols have a significant influence on the measurement error. For instance, variations of table height or slice thickness strongly influence on the results, while parameters such as exposure time or dose showed no appreciable effect. Furthermore, the dimensional measurement errors in the clinical CT systems were much larger than in an industrial CT system. In conclusion, it is important to be aware of the influence of different scanning parameters on the measurement result, if a clinical CT system is used for dimensional metrology. However, the deviations need to be related to the individual diagnostic task and it is important to consider, that the dimensional accuracy of clinical CT systems are not always of great relevance for all kinds of medical applications.<br